Religion and Disparities: Considering the Influences of Islam on the Health of American Muslims - Padela, Aasim I. (Journal of religion and health, 2013)
Both theory and data suggest that religions shape the way individuals interpret and seek help for their illnesses. Yet, health disparities research has rarely examined the influence of a shared religion on the health of individuals from distinct minority communities. In this paper, we focus on Islam and American Muslims to outline the ways in which a shared religion may impact the health of a racially, ethnically, and socioeconomically diverse minority community. We use Kleinman's "cultural construction of clinical reality" as a theoretical framework to interpret the extant literature on American Muslim health. We then propose a research agenda that would extend current disparities research to include measures of religiosity, particularly among populations that share a minority religious affiliation. The research we propose would provide a fuller understanding of the relationships between religion and health among Muslim Americans and other minority communities and would thereby undergird efforts to reduce unwarranted health disparities.